LITERATUR REVIEW: KEBIASAAN OLAHRAGA PADA IBU HAMIL TRISEMESTER III - Anggit Satriyo Yudhono (Cahaya Ilmu Bangsa Institute, 2024)
Pregnancy as an effort to carry on offspring through a legal marriage. A high-risk pregnancy is a pregnancy that has a greater risk of causing illness, disability, and even death of both mother and baby. Pregnant women in the third trimester experience many complaints such as hormonal changes, starting to feel pain around the lower back, the elasticity of the pelvic muscles and ligaments for normal delivery, and excessive anxiety in dealing with childbirth. Efforts to overcome this, among others, can be done with regular exercise in accordance with the abilities of pregnant women. For example, pregnancy exercise, walking, and yoga for pregnant women. This article uses a literature review method that takes primary data from research that has been published in Google indexed journals and the Garuda portal for research articles from within the country. Writing this article aims to review and review 9 articles related to the relationship between exercise habits in pregnant women and their pregnancy complaints in the third trimester. Then from the twelve articles it was concluded that there was a relationship between exercise habits in pregnant women and complaints of pregnancy in the third trimester